2020
DOI: 10.1111/bcpt.13453
|View full text |Cite
|
Sign up to set email alerts
|

Renin‐angiotensin system blockade modulates both the peripheral and central components of neuropathic pain in rats: Role of calcitonin gene–related peptide, substance P and nitric oxide

Abstract: Neuropathic pain (NP) is defined as "the pain caused by a lesion or disease of the somatosensory nervous system". 1 This broad definition covers peripheral and central aspects of pain. The peripheral nerve injury can lead to maladaptation at every point through the pain axis, 2 and hence, profound CNS alterations and central sensitization can occur. 3 However, it has been suggested that central sensitization acts rather as an amplifier of the peripheral signals, and not an independent pain generator in periphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 59 publications
0
10
1
Order By: Relevance
“…Paw withdrawal latency was recorded in seconds. The brief normal response was given a value of 0.5 s and the cut-off point was set at 20 s (Hegazy et al, 2020).…”
Section: Mechanical Hyperalgesia (Pinprick Test)mentioning
confidence: 99%
“…Paw withdrawal latency was recorded in seconds. The brief normal response was given a value of 0.5 s and the cut-off point was set at 20 s (Hegazy et al, 2020).…”
Section: Mechanical Hyperalgesia (Pinprick Test)mentioning
confidence: 99%
“…Further, we investigated the antioxidant potential of both extracts in CCI model. Our previous studies showed that catalase is decreased while, NADPH oxidase-1 (NOX-1) is increased in sciatic nerve and brain stem of CCI rats 6,10,11 . Catalase enzyme is one of the endogenous antioxidant enzymes present in peroxisomes and catalyzes the breakdown of H 2 O 2 to H 2 O and O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…. As detailed in our recent study 11 , a force was applied gently to the mid-plantar surface of the injured hind paw by bent gauge to avoid damaging the skin. Paw withdrawal duration (s) was recorded with a minimum value of 0.5 s (for the brief normal response) and a maximum value of 20 s.…”
Section: Mechanical Hyperalgesia (Pinprick Test)mentioning
confidence: 99%
See 1 more Smart Citation
“…Spontaneous paw lifting and flinching/licking were examined according to previous reports (Hegazy et al, 2020; Labuz & Machelska, 2013; Murai et al, 2016). In brief, a mouse was placed in an open‐topped transparent glass chamber and allowed to move freely for 20 min before being observed.…”
Section: Methodsmentioning
confidence: 99%